Unraveling the asymmetry of Mona Lisa smile. (November 2019) - Marsili, Luca; Ricciardi, Lucia; Bologna, Matteo
Abstract: The Mona Lisa portrait, by Leonardo da Vinci, is one of the most famous paintings in the world. Over the years, there have been a number of debated topics on the painting, including the valence of the emotion expressed on her face. Nevertheless, the most recent interpretations agree that Mona Lisa expression is happiness. The smile asymmetry of Mona Lisa is another remarkable feature of the painting. We here asked forty-two healthy raters to judge which of the six basic emotions (or neutral expression) was expressed by the chimeric images of the left or right lower hemi face. We collected chosen responses, confidence levels and reaction times. Our results indicate that happiness is expressed only on the left side. According to some influent theories of emotion neuropsychology, we here interpreted the Mona Lisa asymmetric smile as a non-genuine smile, also thought to occur when the subject lies. Given that Leonardo was a great observer of human physiognomy we speculate on the intriguing possibility that Leonardo already knew the true meaning of asymmetric smile. Thus, Mona Lisa asymmetric smile could represent a stratagem Leonardo deliberately used to hold cryptic and enigmatic messages. Although the Mona Lisa smile continues to attract the attention of its observers, the true message it conveys remains elusive and many unsolved mysteries remain to be elucidated, perhaps via the knowledge of emotion neuropsychology.